(untitled) (TAMADDUN NURI JURNALI, 2025)
Schopenhauer’s doctrine of ideas and philosophy of nature constitutes an important part of his metaphysical system. In this system, nature is conceived as primordial forces manifesting through the forms of space and time. Ideas, in turn, represent the fundamental forces of nature as the “eternal gaze” that exists beyond space and time. According to Schopenhauer, the world is a manifestation of the “world will”, in which the struggle for existence and suffering have an ontological foundation. The human being, endowed with intellectual capacity, is able to negate this will and attain freedom. This doctrine illustrates the complex unity of aesthetics, ontology, and the philosophy of nature.